APPLICATION OF THEORY OF PROBABILITY IN SOLVING ECONOMIC PROBLEMS - Yuldashev Sanjarbek Arslon o‘g‘li (Galaxy International Interdisciplinary Research Journal, 2023)
The article is devoted to the disclosure of the importance of probability theory in economics, as well as the rationale for its use in solving various problems, namely problems in the areas of credit and insurance. The historical moments of the appearance of the theory of probability are described, as well as the use of methods of the theory of probability where it is possible to create and analyze probabilistic models of actions or phenomena. Due to the fact that with the help of probability theory it is possible to solve various issues related to the study of controversial and imperceptible interrelations of various events and phenomena in different branches of science, it became possible to accurately determine the fluctuations of such economic indicators as demand, supply, prices. For a more detailed study of the application of the theory of probability in practice, the authors of the article examined in detail the solution of problems both in the field of lending and in the field of insurance.